Developing questions of high order thinking skill using adventure story narrative text for junior high school students in Palembang - Octa Risfa Ria Ringkisa; Machdalena Vianty; Bambang A. Loeneto (University of Kuningan, 2020)
The aim of this study was to develop questions of high order thinking skill using adventure story narrative text based on Bloom’s Taxonomy framework. The research method applied was the developmental research developed by Akker (1999). The procedure of the study consisted of three stages, analysis, design, and evaluation. Formative evaluation by Tessmer was conducted to see the validity, practicality, and whether or not the developed product had potential effect to the students. The subject of this study was eighth grade students at SMP N 17 Palembang. The sample of the study was selected purposively based on the category of their English proficiency i.e: low, medium, and high English proficiency. Document related to Higher Order Thinking questions, students’ need, and students’ reading level were analyzed. The results of the analysis became the basis for designing the developed questions. The prototype I, the developed question as the beginning design was validated by 2 experts (expert review) and stated that the prototype 1 consists of 60 questions are valid with average score 4.3, and appropriate to be used. In one-to-one stage, prototype II was tested on 3 students, there were 10 questions that needed to be revised because the students had difficulty understanding what was being asked by the questions. The result of revised questions was called Prototype II. In a small group stage, Prototype II was tested on 6 students, there were 11 questions need to revised, the revised question then produced prototype III. Field test stage aimed to evaluate potential effect of the developed questions. The judgment of potential effect was seen from the mean score of the students in the field test. The results showed that students’ average score was 73. It means that the developed questions of high order thinking skill was categorized as very had high potential effect to the students.